THE NEED FOR INTERACTIVE TEACHING METHODS IN MODERN EDUCATION (SCIENCE TIME JOURNAL, 2026)
This article highlights the importance of using interactive teaching methods when working with today’s youth in secondary schools and higher education institutions. It emphasizes that traditional teaching alone is no longer sufficient; modern, innovative technologies are required. Interactive methods increase student engagement, motivation, and learning outcomes. The article presents several practical interactive techniques that can be applied in language and literature classes.